2.45 GHz wearable rectenna array design for microwave energy harvesting - Syahirah Shawalil; Khairul Najmy Abdul Rani; Hasliza A. Rahim (Institute of Advanced Engineering and Science, 2019)
This paper presents a design of a wearable textile microstrip patch rectifying antenna (rectenna) array operating for wireless body area network (WBAN) at the center frequency, fc of 2.45 GHz. Precisely, jeans or denim with the relative permittivity, = 1.70 and thickness of 1.00 mm is chosen as a substrate attached to SheildIt Super as a conductive material with the thickness, h of 0.17 mm and conductivity of 6.67 105 S/m, respectively. In the first stage, a microstrip patch antenna array layout with the inset fed technique is designed and simulated by using the Keysight Advanced Design System (ADS) software. In the second stage, a wearable textile microstrip patch antenna array is fabricated, integrated, and hidden inside the jeans fabric. In the third stage, the rectifier circuit layout on the flame retardant-4 (FR-4) printed circuit board (PCB) with the dielectric constant, = 4.7, thickness, h = 1.6 mm, and loss tangent, δ = 0.018 that can generate radio frequency-direct current (RF-DC) conversion is designed and simulated using the ADS software Each simulation result and fabrication measurement shows that the designed antenna array characteristics are suitable for an industrial, scientific, and medical radio (ISM) band by having the reflection coefficient, S11 less than -10 decibel (dB) at the respective resonant frequency, fr. Moreover, through simulation, the output DC voltage for the bridge rectifier circuit is from 132 mV to 5.01 V with the corresponding power conversion efficiency (PCE) between 3.48% and 50.20% whereas for the voltage doubler rectifier, the output DC voltage is from 417 mV to 2.91 V with the corresponding PCE between 34.78% and 53.56%, respectively.